Reentrant liquid condensate phase of proteins is stabilized by hydrophobic and non-ionic interactions - Georg Krainer (Nature Portfolio, 2021)
Elucidating the molecular driving forces underlying liquid–liquid phase separation is a key objective for understanding biological function and malfunction. Here the authors show that a wide range of cellular proteins, including FUS, TDP-43, Brd4, Sox2, and Annexin A11, which form condensates at low salt concentrations, can reenter a phase-separated regime at high salt concentrations.